OsRELA Regulates Leaf Inclination by Repressing the Transcriptional Activity of OsLIC in Rice - Zhu, Chen-li; Xing, Bao; Teng, Shou-zhen; Deng, Chen; Shen, Zhen-yong; Ai, Peng-fei; Lu, Tie-gang; Zhang, Sheng-wei; Zhang, Zhi-guo (Frontiers in Plant Science, 2021)
Leaf angle is one of the most important agronomic traits in rice, and changes in leaf angle can alter plant architecture to affect photosynthetic efficiency and thus determine grain yield. Therefore, it is important to identify key genes controlling leaf angle and elucidate the molecular mechanisms to improve rice yield. We obtained a mutant rela (regulator of leaf angle) with reduced leaf angle in rice by EMS mutagenesis, and map-based cloning revealed that OsRELA encodes a protein of unknown function. Coincidentally, DENSE AND ERECT PANICLE 2 (DEP2) was reported in a previous study with the same gene locus. RNA-seq analysis revealed that OsRELA is involved in regulating the expression of ILI and Expansin family genes. Biochemical and genetic analyses revealed that OsRELA is able to interact with OsLIC, a negative regulator of BR signaling, through its conserved C-terminal domain. OsRELA is located downstream of OsLIC. The binding of OsRELA can activate the expression of downstream genes repressed by OsLIC, and the conserved C-terminal domain of OsRELA is essential for its function. Our results suggest that OsRELA can act as a transcriptional regulator and is involved in the regulation of leaf inclination by regulating the transcriptional activity of OsLIC.